APPLICATION OF EXERCISE TRAINING METHODS FOR IMPROVING STUDENTS AND ACHIEVEMENTS STUDENT LEARNING (Study on Information and Communication Technology Class VIII SMP Negeri 11 Kaur) - Palti Ovu Sukisma; Johanes Sapri (UNIB Press, 2018)
This study aims to (1) describe to increase student attention on ICT learning in class VIII SMP Negeri 11 Kaur (2) describes to improve student achievement in learning ICT in class VIII SMP Negeri 11 Kaur (3) describes effective implementation of learning method exercises to improve student achievement in learning ICT in class VIII SMP Negeri 11 Kaur. The research conducted is a classroom action research combined with quasi experiment. The subjects of this study are the students of class VIII a and class VIII b SMP Negeri 11 Kaur as PTK classes and experimental classes. While class VIII c SMP Negeri 11 Kaur, as a control class. Data collection techniques in this study were conducted in the following way: Observation, Observation is a method of data collection using observation of the object of research. to observe student activeness. The test of learning achievement, test as a means of assessment in the form of questions given to students to get answers from students in the form of oral, written, or action tests. The results of this study indicate that the implementation of LKS assisted training methods to: (1) improve the ability of attention on ICT learning of students, (2) Application of LKS assisted training methods can improve student achievement in ICT learning, (3) student learning achievement on learning ICT class VIII SMP Negeri 11 Kaur.